Irrational thoughts as a predictor of depression and burnout in health practitioners - Al-Owayied, AlReem Abdullah; Al-Rajhi, Saleh Mohammed (Journal of Educational and Psychological Sciences, 2025)
The current research aims to identify the relationship between the following variables (irrational beliefs and burnout, burn out and depression, and the prevalence of Irrational Beliefs and their relationship to depression and burnout among health practitioners), The sample of the research consisted of (92) of health practitioners at KFMC Riyadh, The researcher used irrational beliefs scale and beck depression scale and maslach burnout inventory, The researcher used Correlative descriptive approach, Results showed that there is a statistically significant positive correlation between the Irrational Beliefs and depression and burn out.